P10.19 Can hsv-2 seropositivity be used as a biological marker of sexual behaviour? findings from a seroprevalence survey in england. (13th September 2015) - Woodhall, SC; Murphy, G; Craig, R; Mindell, JS; Soldan, K; Johnson, AM; Nardone, A
Abstract : Introduction: Reliable measures of sexual behaviour aid understanding of differences in sexually transmitted infections between groups or over time, but are often difficult or infeasible to collect. Antibody to herpes simplex virus type 2 (HSV-2) has been proposed as a marker of sexual behaviour. We investigated the seroepidemiology of HSV-2 in England to explore the use of HSV-2 as such a marker. Methods: Anonymised sera from 16–44 year-old participants in the Health Survey for England (HSE) in 2010 and 2012, a series of nationally-representative household surveys, were tested for anti-HSV-2 antibodies using the HerpeSelect2 IgG ELISA. Factors associated with seropositivity were investigated using logistic regression Results: HSV-2 seropositivity increased with age up to 15% (95% CI: 11%–19%) in women and 9% (6%–14%) in men aged 40–44 years. Seropositivity was higher in those with more sexual partners over the lifetime in women (1.4% in those with 0 vs. 14% in those with ≥10 lifetime sexual partners, p = 0.018) but not in men (5% vs. 7%, p = 0.683). There was no difference by number of partners in the last year or by recent condom use. Women of black or black British ethnicity had around 3-times higher odds of being seropositive than those of white ethnicity (24% vs. 10%, odds ratio [OR]:2.96, 95% CI: 1.16–7.54; p = 0.023). No difference by ethnicity was noted among men. Conclusion: Our findings suggest antibodies to HSV-2 may be a useful marker for number of lifetime sexual partners in women but not in men. There was less evidence to support the use of HSV-2 as a marker for recent sexual risk behaviour. These data can be used to power future analyses using HSV-2 as a marker of sexual behaviour in women. Although detailed analyses by ethnicity were limited by sample size, the differential risk of seropositivity by ethnicity is of interest and warrants further investigation. Disclosure of interest statement: The study was funded by the Health Protection Agency (now part of Public Health England). No pharmaceutical or diagnostic company grants were received in the development of this study.